Selection and evaluation of the effects of NaCl and pH on the inorganic phosphate-solubilizing bacteria isolated from the wild rice rhizosphere in Dong Thap province - Nguyễn, Hồng Xuyên; Đỗ, Tấn Khang; Trần, Thị Giang (Hue University Journal of Science: Natural Science, 2026)
This study aimed to screen and select inorganic phosphate-solubilizing bacteria (PSB) isolated from the rhizosphere soil of wild rice (Oryza rufipogon) collected in Gao Giong commune and My Hiep commune, Dong Thap province, Vietnam, and to evaluate the effects of salinity and pH on their phosphate-solubilizing capacity. A total of 34 PSB isolates were obtained on NBRIP medium supplemented with Ca₃(PO₄)₂, exhibiting considerable diversity in colony morphology. Phosphate solubilization was assessed using the phosphate solubilization index (PSI) at 5, 10, and 15 days after inoculation, with PSI values ranging from 1.2 to 3.2 at day 10. Five promising isolates (GG6.2, GG7.6, XQ4.1, XQ4.7, and XQ5.3) producing more than 1,000 mg/L of soluble phosphate were selected for further evaluation under different NaCl concentrations (0–1%) and pH levels (3–9). The selected isolates maintained phosphate solubilization of approximately 100 mg/L at 1% NaCl after 10 days, indicating moderate salt tolerance. In contrast, phosphate-solubilizing efficiency markedly declined under acidic and alkaline conditions; soluble phosphate concentrations were below 100 mg/L at pH 3 and decreased more severely at pH 8–9 compared with neutral pH. These results highlight that neutral pH is optimal for phosphate solubilization by the selected isolates. Based on 16S rRNA gene sequencing, isolates GG6.2 and XQ4.7 were identified as Klebsiella, while GG7.6, XQ4.1, and XQ5.3 belonged to the genus Mammaliicoccus.